2003
DOI: 10.1046/j.1529-8817.2003.02018.x
|View full text |Cite
|
Sign up to set email alerts
|

CERAMIUM INKYUII SP. NOV. (CERAMIACEAE, RHODOPHYTA) FROM KOREA: A NEW SPECIES BASED ON MORPHOLOGICAL AND MOLECULAR EVIDENCE1

Abstract: Ceramium inkyuii sp. nov. is newly described based on samples collected from the east coast of Korea and compared with similar species such as C. paniculatum and C. tenerrimum. The new species is characterized by pseudo‐dichotomously branched thalli with a twist in the upper part, a single row of spines on the abaxial side, strongly inrolled apices, and the presence of gland cells. In contrast, C. paniculatum has alternate branches and lacks gland cells, and C. tenerrimum is spineless and also lacks gland cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 17 publications
1
28
0
2
Order By: Relevance
“…Compared to other Ceramium species from the same phylogenetic clade (Figure 1), C. sungminbooi is recognized by the following characteristics: thalli with pseudo-dichotomous branches, apices that are slightly incurved, 4-5 pericentral cells, three cortical cells per node, emergent tetrasporangia that arise adaxially or whorled, and female gametophytes that are occasionally mixed-phase with tetrasporangia. Discrimination of Ceramium species using rbcL sequences has been demonstrated by previous studies (Cho et al 2003a,b, Barros-Barreto et al 2006, Cho et al 2008, Yang et al 2009, Wolf et al 2011, Won and Cho 2011. In this study rbcL sequences from Korea, Oregon, California, Norway, and Denmark were found to be identical, but highly diverged from the lectotype specimen of C. cimbricum, as well as from other previously published sequences of Ceramium.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Compared to other Ceramium species from the same phylogenetic clade (Figure 1), C. sungminbooi is recognized by the following characteristics: thalli with pseudo-dichotomous branches, apices that are slightly incurved, 4-5 pericentral cells, three cortical cells per node, emergent tetrasporangia that arise adaxially or whorled, and female gametophytes that are occasionally mixed-phase with tetrasporangia. Discrimination of Ceramium species using rbcL sequences has been demonstrated by previous studies (Cho et al 2003a,b, Barros-Barreto et al 2006, Cho et al 2008, Yang et al 2009, Wolf et al 2011, Won and Cho 2011. In this study rbcL sequences from Korea, Oregon, California, Norway, and Denmark were found to be identical, but highly diverged from the lectotype specimen of C. cimbricum, as well as from other previously published sequences of Ceramium.…”
Section: Discussionsupporting
confidence: 54%
“…The genus is widespread, distributed from tropical to boreal coasts around the world (Cho et al 2003a). Ceramium is characterized by erect and terete filamentous thalli with complete or incomplete cortication, rounded cortical cells, and irregularly shaped periaxial cells (Kylin 1956).…”
Section: Introductionmentioning
confidence: 99%
“…The rbcL gene was amplified using the primer combinations F7-R753 and F645-Rrbcst, as listed in Lin et al (2001), and was sequenced with the primers F7, F645, F993, R376, R753, R1150, and RrbcStart (Freshwater and Rueness 1994, Lin et al 2001, Gavio and Fredericq 2002. PCR and sequencing protocols were as described in Cho et al (2003). Sequences were determined for both forward and reverse strands using an ABI Prism 3100 Genetic Analyzer (PE Applied Biosystems, Foster City, CA, USA).…”
Section: Molecular Studymentioning
confidence: 99%
“…Sequencing primers used were: F7, F645, F993, R367, R753, R1150, RrbcS start (Freshwater & Rueness, 1994;Lin et al, 2001;Gavio & Fredericq, 2002). Amplification conditions followed Cho et al (2003). Sequences were determined for both forward and reverse strands using an ABI Prism 3100 Genetic Analyzer (PE Applied Biosystems, Foster City, CA) with the ABI Prism BigDye TM Terminator Cycle Sequencing Ready Reaction Kit (PE Applied Biosystems).…”
Section: Molecular Studymentioning
confidence: 99%